Solved

# Removing the exponent

Posted on 2011-04-18
398 Views
This is the question and the answer, but I don't understand it.

With an exponent of ^2 it's a simple matter -3(-2)^2 = -3(4). But the problem below has both a negative exponent and an exponent less than 2. Can someone help me understand first how a negative exponent effects a problem and then how an exponent of less than 2 effects a problem? Thanks.

-3(-2)^-1 = -(3/-2)
0

LVL 31

Assisted Solution

a^(-1) is defined to be 1/a

-3 * (a)^(-1) = -3/a

Let a = -2
-3 * (-2)^(-1) = -3/(-2) = +3/2
0

LVL 31

Accepted Solution

Now consider a^(-2). That is just 1/( a^2 )
So, if a = -2, then a^(-2) = 1/( a^2 ) = 1/(   (-2)^2   ) = 1/(   -2*-2 ) = +1/4
0

LVL 31

Assisted Solution

Here is something that may help you understand why the negative exponent was defined that way.

Consider a^5/a^3 = (aaaaa)/aaa = aa = a^2
which leads to a natural formula to remember:  a^n / a^k = a^(n-k)i.e., a^5/a^3 = a^(5-3) = a^2

Now consider a^3/a^5 = aaa/(aaaaa) = 1/(aa) = 1/a^2
But, if you try to use the above formula, you get a^3/a^5 = a^(3-5) = a^(-2)

So, someone said, let's define a negative exponent to be:  a^(-n) = 1/a^n
and since this one formula seemed to fit well into algebra, it stuck.
0

LVL 31

Expert Comment

Here's a little more discussion of negative exponents:
http://www.mathsisfun.com/algebra/negative-exponents.html

0

Author Comment

Thanks for your help. I think I understand this a little better.
0

LVL 31

Expert Comment

You're welcome.
BTW - I tend not to try to remember a lot of formulas. Instead I try to understand their derivation, and use that approach when thinking about these types of problems.
0

## Write Comment

Please enter a first name

Please enter a last name

We will never share this with anyone.

## Featured Post

### Suggested Solutions

How to Win a Jar of Candy Corn: A Scientific Approach! I love mathematics. If you love mathematics also, you may enjoy this tip on how to use math to win your own jar of candy corn and to impress your friends. As I said, I love math, but I gu…
This is a research brief on the potential colonization of humans on Mars.
In this seventh video of the Xpdf series, we discuss and demonstrate the PDFfonts utility, which lists all the fonts used in a PDF file. It does this via a command line interface, making it suitable for use in programs, scripts, batch files — any pl…
Access reports are powerful and flexible. Learn how to create a query and then a grouped report using the wizard. Modify the report design after the wizard is done to make it look better. There will be another video to explain how to put the final p…

#### 761 members asked questions and received personalized solutions in the past 7 days.

Join the community of 500,000 technology professionals and ask your questions.

#### Need Help in Real-Time?

Connect with top rated Experts

15 Experts available now in Live!